Cystic Lymphangioma Of The Right Parotid Gland In An Infant: A Rare Entity With Classic Imaging Features - Davra, MD, Sanket Vinubhai; Ganeshwala, Uday; Gupta, Tarun (Journal of Neonatal Surgery, 2025)
Cystic lymphangioma is a benign lesion consisting of multiple lymphatic spaces. The primary site of lymphangioma at parotid gland is extremely unusual and till date, there are only very few cases of infant cystic lymphangioma of the parotid. In this study, we presented the case of a 7-month-old female patient with cystic lymphangioma of the right parotid gland since birth which is a rare entity and its classic imaging features in detail. USG revealed a well-defined multiloculated, multiseptated anechoic cystic lesion involving the right parotid gland, likely involving both superficial and deep lobes. The lesion measured approximately 45 x 40 × 31 mm (CC x AP × TR). Inferiorly, the lesion extended into the right submandibular region, causing mass effect on the ipsilateral submandibular gland, which was displaced anteromedially. CECT showed well-defined multilobulated, multiseptated hypodense cystic lesion with attenuation values of 10–20 HU involving the right parotid gland, measuring approximately 48 × 43 × 35 mm (CC × AP × TR). The lesion demonstrated thin, imperceptible walls and internal septations. As per this study, USG can be recommended for initial non-invasive imaging that leads to a diagnosis. To evaluate the extent of the lesion, CECT had been used in this study which provided better diagnosis. However, the definitive diagnosis can be achieved with final histopathological examination